50 years of Ms. : the best of the pathfinding magazine that ignited a revolution - Spillar, Katherine; Steinem, Gloria (Alfred A. Knopf, 2023)
"A decade-by-decade compendium of articles, fiction, poetry, and art from Ms. Magazine"--